THE EFFECT OF USING EGRA TECHNIQUE IN READING DESCRIPTIVE TEXT AT THE GRADE XI OF SMA NEGERI 1 ANGKOLA BARAT - Siagian, Abdul Rahman (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The study was conducted in SMA Negeri 1 Angkola Barat. The aims of this research was to find out if there a significant Effect of Using EGRA technique on Students’ descriptive text. The writer carried out in quantitative approach by applying experimental method. The population of this research was the grade XI. They were 178 students, the writer used cluster sampling technique to get the sample. The samples were 32 students. The reading descriptive text was applied as the instrument, the writer used “t” test formula. Based on the data analyzed, it can be found that (1 data description showed that the mean scores of students in reading Descriptive text without using EGRA technique was in enough criteria, (2) the data description showed that the mean scores of students in reading descriptive text by using EGRA technique was in good criteria, and (3) There was a significant effect of using EGRA technique in reading descriptive text at the Grade XI of SMA Negeri 1 Angkola Barat or t0 was greater than the score of tt. It meant that the hypothesis was accepted.